Prevention of vaginal and rectal herpes simplex virus type 2 transmission in mice: mechanism of antiviral action - Ceña-Diez R (Dove Medical Press, 2016)
Rafael Ceña-Diez,1,* Enrique Vacas-Córdoba,1,* Pilar García-Broncano,1,2 FJ de la Mata,3 Rafael Gómez,3 Marek Maly,4 Mª Ángeles Muñoz-Fernández11Molecular Immunobiology Laboratory, General Universitary Hospital Gregorio Marañon, Health Research Institute Gregorio Marañon, Spanish HIV HGM BioBank, Networking Research Center on Bioengineering, Biomaterials and Nanomedicine (CIBER-BBN), 2Viral and Immune Infection Unit Center, Institute of Health Carlos III, Majadahonda Campus, Molecular Immunobiology Laboratory, General Universitary Hospital Gregorio Marañon, 3Organic and Inorganic Chemistry Department, Alcala University, University Campus Alcala de Heneras, Networking Research Center on Bioengineering, Biomaterials and Nanomedicine (CIBER-BBN), Madrid, Spain; 4Faculty of Science, J.E. Purkinje University, Ústí nad Labem, Czech Republic*These authors contributed equally to this work Abstract: Topical microbicides to stop sexually transmitted diseases, such as herpes simplex virus type 2 (HSV-2), are urgently needed. The emerging field of nanotechnology offers novel suitable tools for addressing this challenge. Our objective was to study, in vitro and in vivo, antiherpetic effect and antiviral mechanisms of several polyanionic carbosilane dendrimers with anti-HIV-1 activity to establish new potential microbicide candidates against sexually transmitted diseases. Plaque reduction assay on Vero cells proved that G2-S16, G1-S4, and G3-S16 are the dendrimers with the highest inhibitory response against HSV-2 infection. We also demonstrated that our dendrimers inhibit viral infection at the first steps of HSV-2 lifecycle: binding/entry-mediated events. G1-S4 and G3-S16 bind directly on the HSV-2, inactivating it, whereas G2-S16 adheres to host cell-surface proteins. Molecular modeling showed that G1-S4 binds better at binding sites on gB surface than G2-S16. Significantly better binding properties of G1-S4 than G2-S16 were found in an important position for affecting transition of gB trimer from G1-S4 prefusion to final postfusion state and in several positions where G1-S4 could interfere with gB/gH–gL interaction. We demonstrated that these polyanionic carbosilan dendrimers have a synergistic activity with acyclovir and tenofovir against HSV-2, in vitro. Topical vaginal or rectal administration of G1-S4 or G2-S16 prevents HSV-2 transmission in BALB/c mice in values close to 100%. This research represents the first demonstration that transmission of HSV-2 can be blocked by vaginal/rectal application of G1-S4 or G2-S16, providing a step forward to prevent HSV-2 transmission in humans.Keywords: nanotechnology, dendrimers, G1-S4, G2-S16, HSV-2, microbicide